Low-carbon city initiatives and analyst behaviour: A quasi-natural experiment - Cao, June; Li, Wenwen; Bilokha, Alona (Journal of Financial Stability, 2022)
This paper investigates how environmental regulation and action affect analyst behaviour. Exploiting staggered enactment of low carbon city (LCC) initiatives in a difference-in-differences (DiD) setting, we observe that analyst forecast accuracy (dispersion) is significantly lower (greater) for client firms headquartered in cities covered by the LCC pilot programme, especially among firms with a low-quality information environment. The LCC effort affects analyst behaviour via increased firm risk and reduced earnings predictability, causing enhanced site visits and coverage. The results are stronger in cities with more rigorous enforcement and regulation intensity, for private firms with high business complexity and in heavily polluting industries. Results are robust to DiD models with entropy balancing matching, placebo tests, parallel trend tests, and a battery of fixed effects. Collectively, they reveal that environmental regulation has real impacts on analyst forecast behaviour.